E-learning satisfaction: a perspective on UiTM E-PJJ students / Surianor Kamaralzaman … [et al.] - Kamaralzaman, Surianor; Abdul Talib, Faizah Eliza; Che Mamat, Rusalbiah; Mohi@Mohyi, Zurinawati; Dahalan, Muhammad Asyraf (Penerbit UiTM (UiTM Press), 2018)
E-PJJ is a form of e-learning system that offers working adults to engage in UiTM’s distance learning programme. The system provides the students access to the course materials and lecture notes as well as to the interaction among students, and between students and the lecturers. The purpose of this study was to identify student’s satisfaction toward e-learning programme offered by Institute of Neo Education (iNED). A survey questionnaire was administered among the respondents who are undergraduates in the e-PJJ degree programmes, iNED at UiTM Shah Alam. This research examined the relationship of delivery method, content, communication facilities and system operations towards the level of student’s satisfaction. The findings showed a positive relationship between delivery methods, content, communication facilities, also system operations and student’s satisfaction. In addition, delivery method scored a moderate positive relationship towards student’s satisfaction. This study might be very useful for the institution that offer similar programme, namely distance learning that requires ICT to distribute knowledge, to teach and learn. All the shortcomings in the distance learning would be resolved for better education and service quality for future students.